Pengaruh Reputasi KAP, Ukuran Perusahaan, Opini Audit Tahun Sebelumnya, dan Profitabilitas terhadap Opini Audit Going Concern: (Studi Empiris Pada Perusahaan Properti & Real Estate yang Terdaftar pada Bursa Efek Indonesi Periode 2019 – 2023) - Celine Franssy Odelia Soraya; Anggoro Yuli Cahyono (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The purpose of this research is to get empirical evidence about the effect of public accounting firm reputation, company size, previous year audit opinion, and profitability to going concern audit opinion. The population in this research are based empirical studies on property and real estate companies listed in Indonesia Stock Exchange on period 2019 – 2023. The theory used in this research is agency theory and signaling theory. The method of determining sample in this research uses purposive sampling method with 44 sample property and real estate companies that have fulfilled the criteria. For this research using logistic regression analysis techniques and using statistical test tools SPSS version 22. The results of this research indicate that previous year audit opinion variable have a significant effect on the going concern audit opinion, while public accounting firm reputation, company size, and profitability variables have no effect on going concern audit opinion.